Nanoparticles of the poly([N-(2-hydroxypropyl)]methacrylamide)-b-poly[2-(diisopropylamino)ethyl methacrylate] diblock copolymer for pH-triggered release of paclitaxel. Issue 27 (18th June 2015) - Jäger, Alessandro; Jäger, Eliézer; Surman, František; Höcherl, Anita; Angelov, Borislav; Ulbrich, Karel; Drechsler, Markus; Garamus, Vasil M.; Rodriguez-Emmenegger, Cesar; Nallet, Frédéric; Štěpánek, Petr
Abstract : The potential of self-assembled nanoparticles for in vitro cytostatic activity has been explored on cancer cells. Abstract : The potential of self-assembled nanoparticles (NPs) containing the fine tunable pH-responsive properties of the hydrophobic poly[2-(diisopropylamino)ethyl methacrylate] (PDPA) core and the protein repellence of the hydrophilic poly[ N -(2-hydroxypropyl)methacrylamide] (PHPMA) shell for in vitro cytostatic activity has been explored on cancer cells. The amphiphilic diblock copolymer poly[ N -(2-hydroxypropyl)methacrylamide]- b -poly[2-(diisopropylamino)ethyl methacrylate] (PHPMA- b -PDPA) synthesized by a reversible addition–fragmentation chain transfer (RAFT) technique allows for excellent control of the polymer chain length for methacrylamides. The PHPMA- b -PDPA block copolymer dissolved in an organic solvent (ethanol/dimethylformamide) undergoes nanoprecipitation in phosphate buffer saline (PBS, pH ∼ 7.4) and self-assembles into regular spherical NPs after solvent elimination. The NPs' structure was characterized in detail by dynamic (DLS), static (SLS) and electrophoretic (ELS) light scattering, small angle X-ray scattering (SAXS), and cryo-transmission electron microscopy (cryo-TEM). The PHPMA chains prevented the fouling of proteins resulting in a remarkable stability of the NPs in serum. On decreasing pH the hydrophobic PDPA block becomes protonated (hydrophilised) in a narrow range of pH (6.51 < pH < 6.85; ΔpH ∼ 0.34) resulting in the fast disassembly of the NPs and chemotherapeutic drug release in a simulated acidic environment in endosomal and lysosomal compartments. A minimal amount of drug was released above the threshold pH of 6.85. The in vitro cytotoxicity studies showed an important increase in the activity of the NPs loaded with drug compared to the free drug. The particle's size below the cut-off size of the leaky pathological vasculature (less than 100 nm), the excellent stability in serum and the ability to release a drug at the endosomal pH with concomitant high cytotoxicity make them suitable candidates for cancer therapy, namely for treatment of solid tumours exhibiting high tumor accumulation of NPs due to the Enhanced Permeability and Retention (EPR) effect.